Ответы и объяснения

2014-01-22T14:03:14+04:00
 \sqrt{(-18+11x)} = x
(-18+11x) =  x^{2}  \\  x^{2} -11x +18 = 0
решаем квадратное уравнение
D = b^2-4ac = 49
x_{1,2}= \frac{-b\pm\sqrt{D}}{2a} = \frac{11\pm\sqrt{49}}{2}  = \frac{11\pm7}{2}
x_1 = 9,\; x_2 = 2
Проверим ОДЗ
-18+11x  \geq 0 \\ x  \geq 1\frac{7}{11}
подходят оба корня

Ответ:
x_1 = 9,\; x_2 = 2

2014-01-22T14:03:39+04:00
Возведен обе части в квадрат.
-18+11х=х^2
-18+11х-х^2=0
домножим на -1
х^2-11х юмор+18=0
Д =49
х1=11+7/2=9
х2 = 11-7/2=2